Otentisitas Dan Validitas Hadis Dalam Perspektif Ulama Modern - Eko Zulfikar (Jurnal Studi Hadis Nusantara, 2020)
This paper seeks to review the views of modern scholars towards the authenticity and validity of the Prophet’s traditions. Modern scholars are divided into three parts in addressing the hadith in terms of its authenticity and validity using descriptive analytical methods. First, the scholars who have skeptical assumptions about the authenticity of the traditions of the Prophet, represented by Mah}mud Abu> Rayyah. In his work Ad}wa>’ ‘ala> al-Sunnah al-Muh}ammadiyyah, Abu> Rayyah considers all the traditions to be considered inauthentic until proven authenticity. The two, scholars who have non-skeptical assumptions, are represented by Yu>suf alQard}awi> in his work Kaifa Nata’a>mal ma’a al-Sunnah al-Nabawiyyah. Regarding the validity of the Prophet’s hadith, al-Qard}awi> prefers to act tawaqquf (no comment attitude) when encountering a valid hadith but its meaning is still vague. Third, the scholars who have assumed middle ground. This section is represented by Muh}ammad al-Ghaza>li> in his work al-Sunnah al-Nabawiyyah Baina Ahl al-Fiqh wa Ahl al-H{adi>th, he assumes that even though a hadith has been considered valid in terms of sanad, it is not necessarily valid in terms of death.